Corporate social performance and portfolio management. Issue 9 (14th September 2015) - Teti, Emanuele; Dell'Acqua, Alberto; Etro, Leonardo L.; Andreoletti, Linda Benedetta
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to assess the existence of a relationship between socially responsible behavior of companies and price trends of their stocks. Design/methodology/approach – The analysis is conducted by empirically testing data of environmental, social and governance ratings of a sample of European firms between December 2005 and December 2010. A disaggregate analysis is also performed to infer whether a specific contribution of all the different factors that make a business socially responsible can be observed in the value generation process. Findings – The results show that the application of a sustainable approach are successful in creating value, both to the investor and the issuer companies. Research limitations/implications – Findings of this work are significant with respect to portfolio management, because they suggest, on one hand, the myopia of a short-term approach (short-termism), and on the other hand, the importance of sustainable investing. Originality/value – This paper focusses on the integration that has led many international groups to explicitly include extra-financial risk factors in their decision-making processes, by applying the by the four-factor model on a brand new data set.